Vulnerability assessment methodology for cascade contingencies in power systems (2010)
A blackout is defined as a non-planned or uncontrolled event that causes the outage of great part of a power system 0. Today, as a result of new economic requirements and expansion, power systems are highly interconnected networks operating close to their security and stability limits; so, the consequences of possible blackouts may be catastrophic in social and economic terms 0. In this way, it is necessary the evaluation of the vulnerability of power systems under this kind of events.